Supervisi Model Behaviour dalam Konteks Analisis Supervisi Pendidikan - Samsudin, Dedi Abu; Gunawan, Agus; Supardi, Supardi (EduInovasi: Journal of Basic Educational Studies, 2024)
This literature research article discusses the role and implementation of the Supervision Behaviour Model in the analysis of educational supervision. Behaviour Model Supervision is an approach that not only focuses on supervision, but also aims to increase positive behaviour in the education system. With a focus on teachers, students, and administration, this supervision involves observing teaching practices, social interactions, and communication in the classroom. Through performance evaluation and implementation of corrective actions, behavioural model supervision forms the basis for professional development and character building of students. This article presents a synthesis of literature regarding the concepts, benefits, challenges and solutions in implementing Behaviour Model Supervision, as well as its implications for the quality of education and the development of the education system as a whole.